MSMEs' Strategy for Upgrading Through Product Quality and Marketing Improvements - Rizal Perlambang CNAWP (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving national economic growth through job creation, increasing community income, and strengthening regional economies. However, most MSMEs in Indonesia still face various obstacles in increasing their competitiveness, preventing them from developing into more productive businesses or upgrading their businesses. This study aims to analyze MSMEs' strategies for upgrading their businesses through product quality and marketing improvements. The study employed a qualitative approach with descriptive methods. Data were obtained through in-depth interviews, observations, and documentation studies. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which included data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation, method triangulation, and member checking. The results showed that improving product quality through the use of quality raw materials, product innovation, quality standardization, packaging design improvements, and compliance with product certification and legality increased added value and consumer trust. Furthermore, the implementation of digital marketing strategies through social media, marketplaces, websites, and branding enhancements has been shown to expand market reach, enhance customer interaction, and drive sales growth. This study also found that the success of MSMEs in upgrading is influenced by human resource competency, digital technology utilization, access to financing, government support, and partnerships with various stakeholders. However, challenges such as limited capital, low digital literacy, limited innovation, and increasingly fierce market competition remain major obstacles to MSME development. Therefore, an integrated strategy is needed through product quality improvement, digital transformation, continuous innovation, and marketing strengthening so that MSMEs can increase their competitiveness, expand market access, and make a greater contribution to national economic development.